Assessment of Cognitive Function in Patients with Hypertension from Different Socioeconomic Statuses in India: A Two - Arm Cross-Sectional Study - Vermani, Sonal; Nagendra, Shashank; Naman M Singh, Kritarth; Pandurang Kale, Vinayak (International Journal of Innovative Research in Medical Science, 2018)
Objectives - Age-related decline in cognitive functions is a common phenomenon but not uniform across all domains and varies amongst individuals. Few longitudinal studies have demonstrated the relation between elevated blood pressure and fall in cognitive function, but Indian literature in this regard is scarce. Hence, we conducted this study to determine the prevalence and occurrence of cognitive deficits in hypertensive patients, and its relation with socio-economic status. Methods - This was a two-arm cross-sectional study. 100 patients (hypertensives and normotensives) attending geriatric/medicine out-patient department of a tertiary care centre were recruited. Grading of hypertension was done and details of medication were taken. Presence of psychiatric/neurological complications were noted. Socio-economic status of patients was assessed using Modified Kuppuswamy’s Socioeconomic Scale. Two established psychiatric evaluations namely Addenbrooke’s Cognitive Examination (ACE) and Trail Making Test (TMT) were conducted. Results - Forgetfulness, the most common complaint, was presented by 44% cases but only by 10% controls. Amongst the hypertensives 13 patients had confusion, 2 had aggressive behaviour and 15 had behavioural changes. 94% cases had cognitive impairment in test group compared to 72% in control, by the ACE. The difference in time lag for TMT Part A between cases and controls was statistically significant (P<0.05). For TMT Part B, difference was not significantly different. ACE scores in hypertensives of lower socioeconomic status was significantly less (P<0.05). Conclusion - Assessment revealed significantly high prevalence of cognitive impairment in hypertensives as compared to normotensives. Early identification of cognitive dysfunction may provide considerable benefit to hypertensive patients.